1904
DOI: 10.5962/bhl.title.26209
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of plant morphology; being the Handbook of plant dissection by J. C. Arthur, Charles R. Barnes and John M. Coulter revised and rewritten by Otis W. Caldwell.

Abstract: Anthoceros gametophyte and sporophyte. 5. Porella branches bearing sex-organs and sporophytes. 6. Moss, showing sex-organs and capsule. 7. Pteris or a similar fern, showing leaf, rhizome, sporangia, gametophytes with sex-organs, and young sporophytes. 8. Marsilia or Selaginella, showing structures of male and female gametophytes. 9. Pine, showing wood, needle-leaf, microsporangia, megasporangia, with gametophytes, and young sporophytes. 10. Trillium leaf, root (or onion root), stem, microsporangia, and megaspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…In distal colon epithelium permeabilized with nystatin, the serosal addition of Gd 3+ (100 mM) aected neither basal I K nor the current induced by thē avonol (Figure 7a,b). The latter experiments were conducted in HEPES/Tris buer due to the fact that Gd 3+ ions can be eectively bound by CO 3 27 and PO 4 37 anions (Caldwell et al, 1998).…”
Section: Quercetin Activates Basolateral K + Channelsmentioning
confidence: 99%
“…In distal colon epithelium permeabilized with nystatin, the serosal addition of Gd 3+ (100 mM) aected neither basal I K nor the current induced by thē avonol (Figure 7a,b). The latter experiments were conducted in HEPES/Tris buer due to the fact that Gd 3+ ions can be eectively bound by CO 3 27 and PO 4 37 anions (Caldwell et al, 1998).…”
Section: Quercetin Activates Basolateral K + Channelsmentioning
confidence: 99%
“…In this work it will be shown that like most species of mammals, the African elephant converts benzoic and phenylacetic acid into their glycine conjugates and phenol into its sulphate and glucuronic acid conjugates. In the case of the hyaena phenol, at a level of 10 mg/ kg, forms only sulphate conjugates and is thus similar to the cat, lion, civet and genet and also the caracal [5]. The hyaena also does not acetylate the aromatic amino group of sulphadimethoxine and is in this respect like the domestic dog [6] rather than the cats which acetylate the drug [ 1 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic colours for these stars have been determined using UBV photometric Q method (cf. Johnson & Morgan 1953;Sagar & Joshi 1979) and the calibrations given by Caldwell et al (1993)…”
Section: Interstellar Extinction Towards the Clustersmentioning
confidence: 99%